Capital Structure, Business Risk and Corporate Performance (Case Study on Construction and Real Estate Sector) - Sutrisno Sutrisno (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study is to examine the effect of capital structure and business risk on corporate performance. This study also examined the effect of non debt tax shield (NDTS) and sales growth (SG) on corporate performance with firm size (SIZ) as a control variable. Corporate performance is measured by return on assets (ROA), while capital structure is measured by debt to equity ratio (DER), and business risk meausred by degree of operating leverage (DOL). The population in this study is a company engaged in the construction and real estate sector that listed on the Indonesia Stock Exchange. The samples taken were 32 companies with purposive sampling. observations period for 3 years (2015-2017). Data is processed using ordinary least square (OLS). The results showed on the significance level 0.10, capital structure (DER) had a significant but negative effect on corporate performance. Business risk (DOL) and sales growth (SG) have a significant and positive effect on performance. While non debt tax shield (NDTS) and firm size (SIZ) have no significant effect on corporate performance.